2015
DOI: 10.1089/apc.2014.0306
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an Intimate Partner Violence (IPV) Screening Protocol in HIV Care

Abstract: HIV and intimate partner violence (IPV) epidemics propagate and interact in a syndemic fashion contributing to excess burden of disease and poorer health outcomes. In order to understand the impact of IPV on HIV disease management, a universal screening program was implemented in the Southern Alberta Clinic in May 2009. We evaluated our IPV screening protocol and made recommendations for its usage in HIV care. IPV data obtained from patients were evaluated, supplemented with responses from a subset of in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…We found that more than one-third of participants (39.0%) experienced IPV in the past year. This overall IPV exposure rate is similar to prior studies in persons living with HIV, which utilized different assessment tools [36, 39, 53, 65]. The majority of participants in our study had a predominant HIV risk factor of male-to-male sexual contact.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that more than one-third of participants (39.0%) experienced IPV in the past year. This overall IPV exposure rate is similar to prior studies in persons living with HIV, which utilized different assessment tools [36, 39, 53, 65]. The majority of participants in our study had a predominant HIV risk factor of male-to-male sexual contact.…”
Section: Discussionsupporting
confidence: 85%
“…This phenomenon of mutual IPV has been observed in the context of heterosexual and same-sex relationships, including those of people living with HIV [52], which likely reflects additional complexities within this syndemic that have yet to be explored. In response to these findings, many HIV providers are implementing IPV screening protocols within their clinics in an effort to better identify and assist these individuals [53].…”
Section: Introductionmentioning
confidence: 99%
“…Health advisors were identified as the best placed practitioners to ask about DVA because they provide counseling in relation to risk behaviors such as unsafe sex, alcohol and substance abuse, and depression, all of which can co-occur with DVA (Buller, Devries, et al, 2014). Furthermore, they have time to develop a trusting relationship with patients, which can facilitate disclosure of abuse, a finding which has been reported in a Canadian study of a screening protocol for intimate partner violence in a HIV clinic (Raissi, Krentz, Siemieniuk, & Gill, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, they have time to develop a trusting relationship with patients which can facilitate disclosure of abuse, a finding which has been reported in a Canadian study of a screening protocol for intimate partner violence in an HIV clinic (Raissi et al 2015). The interpersonal skills of the health practitioner was considered more important than gender or sexual orientation.…”
Section: Discussionmentioning
confidence: 98%
“…These guideline recommendations are based on research from multiple health settings. This research includes how to effectively identify those affected by DVA and record DVA safely, in emergency care [ 3 ], antenatal [ 4 ], maternity & sexual health services [ 5 ], HIV clinics [ 6 ], community gynaecology [ 7 ], mental health [ 8 ] and primary care [ 9 ]. Yet globally, clinicians often do not respond adequately to DVA [ 10 ].…”
Section: Introductionmentioning
confidence: 99%